2017
DOI: 10.1145/2963104
|View full text |Cite
|
Sign up to set email alerts
|

Rating Effects on Social News Posts and Comments

Abstract: At a time when information seekers first turn to digital sources for news and opinion, it is critical that we understand the role that social media plays in human behavior. This is especially true when information consumers also act as information producers and editors through their online activity. In order to better understand the effects that editorial ratings have on online human behavior, we report the results of a two large-scale in-vivo experiments in social media. We find that small, random rating mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 64 publications
1
31
1
3
Order By: Relevance
“…Since most platforms reveal the aggregate vote thus far, the initial votes act as a social signal to influence the subsequent voters, forming the basis of social influence bias. We know from prior work that for platforms that reveal social signal, users exhibit a herding effect [23]: the first few votes on content can unduly skew the subsequent votes. Consider a counterfactual scenario, where two "identical" content initially receive dissimilar votes; then, social influence bias implies that the content with higher aggregate vote thus far will receive more upvotes.…”
Section: Voter Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Since most platforms reveal the aggregate vote thus far, the initial votes act as a social signal to influence the subsequent voters, forming the basis of social influence bias. We know from prior work that for platforms that reveal social signal, users exhibit a herding effect [23]: the first few votes on content can unduly skew the subsequent votes. Consider a counterfactual scenario, where two "identical" content initially receive dissimilar votes; then, social influence bias implies that the content with higher aggregate vote thus far will receive more upvotes.…”
Section: Voter Biasmentioning
confidence: 99%
“…There is a plethora of research on detecting and quantifying voter biases in online platforms [51,38,34,43,36,33,59,28,54,57,9,1,23]. Broadly, researchers have adopted one of the following two approaches: 1) conduct experiments to create different voting conditions for studying participants [51,38,43,36,28,1,23]; 2) develop statistical models to analyze historical voting data [34,33,59,54,57,9]. Both approaches have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The voting pattern in the Reddit [14] has been studied to analyze the upvoting of posts from a new page to the front page and behavior of users towards some posts which are getting positive or negative votes.They have studied the posts mentioning Wikileaks and Fox News and to see the impact of negative voting on them, although working on only one month of data. One study related to rating effect on posts and comments [8] revealed that random rating manipulations on posts and comments led to significant changes in downstream ratings leading to significantly different final outcomes -positive herding effects for positive treatments on posts, increasing final ratings on the average, but not for positive treatments on comments, while negative herding effects for negative treatments on posts and comments, decreasing the final ratings on average. Another exploratory study [20] on the dynamics of discussion threads found topical hierarchy in discussion threads, and how it is possible to use them to enhance Web search.…”
Section: Related Workmentioning
confidence: 99%
“…Online, we must rely on ratings provided by previous customers instead. Online rating systems, however, suffer from the known problem of social influence, also termed herding, which expresses the fact that raters tend to be biased by the opinions of previous raters [2,6,8,10,13,17] and which can make online rating systems fickle and sensitive to small variations in early ratings: if the first few reviews of a product happen to swing a certain way (or are purposefully engineered that way in an act of review spamming [9]), this can unduly skew subsequent reviews. This can have severe implications for both customers, who may end up with unsatisfying products, and producers, whose highquality products may end up being bought less than they deserve.…”
Section: Introductionmentioning
confidence: 99%